Memahami Kehadiran: Gabriel Marcel dan Dimensi Kemanusiaan dalam Merawat Orang Sakit - Jani, Berno; Nali, Frederik Agung (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This paper explores the contribution of existentialist philosopher Gabriel Marcel in understanding the human dimension of caring for the sick. In the context of modern healthcare, which tends to emphasize technical and procedural aspects, Marcel’s approach offers a more humanistic perspective, highlighting the importance of presence, personal involvement, and interpersonal relationships. Through key concepts such as “being” versus “having,” “mystery” versus “problem,” and the notion of “presence” in relationships, Marcel invites us to treat patients not merely as objects of care, but as whole subjects undergoing existential struggles. Using a qualitative and reflective-hermeneutic approach, this paper highlights how Marcel’s philosophical values can enrich medical practice, particularly in fostering empathetic, personal, and meaningful care. Ultimately, the paper asserts that caring is not merely a technical act, but an existential calling that demands presence and openness to the mystery of human suffering.